Settlement of disputes peacefully regarding the territorial boundaries between the two countries (analysis of cases of shootings of Indonesian citizens in Timor Leste) - Heri Yuliyanto (Central Research Institute for Agriculture (CeRIA), 2022)
In this research the author uses the Normative Juridical method which uses secondary data as the main material in the preparation of this thesis with Content Analysis techniques, namely secondary data that is interpreted and connected with legal expert opinions to obtain conclusions so as to obtain thorough and comprehensive research results. Based on the results of the research, it is obtained that to resolve the border dispute between the two countries by using conciliation between the two countries by forming a conciliation commission for a span of three months to obtain results about the causes of border disputes caused by the shooting of Indonesian citizens. This conciliation is intended to provide a mandate or order to the conciliation commission about who is responsible for the shooting and then provide a way to determine the territorial boundary between the two countries. The second way is to use an Inquiry involving an independent team, the results of which will be made public for further action. The next step is to use Arbitration which is public if the two methods above are unable to overcome the problem. The arbitration in question is a semi-court to try the perpetrators of the shooting as well as establish a clear boundary between the two countries so that in the future the same dispute does not occur. The effort that can be taken by Indonesia to realize justice for the victims of the shooting is to submit a strong protest note against this shooting case and clarify the incident to Timor Leste if it does not get a good response is to terminate diplomatic relations because of the dangerous nature of the shooting action for peace in the border area. The next step would be a local court for the shooter in the jurisdiction of Timor Leste. This is an effective way to resolve border disputes without resorting to violence.